2021
DOI: 10.4103/sjmms.sjmms_116_20
|View full text |Cite
|
Sign up to set email alerts
|

Profile of glaucoma in the Eastern region of Saudi Arabia: A retrospective study

Abstract: Background: Glaucomas remain asymptomatic until severe, indicating that the actual number of affected individuals may be higher than those diagnosed. Objective: To study the clinical patterns of glaucoma cases in the Eastern Province of Saudi Arabia. Patients and Methods: This retrospective study was conducted at King Fahd Hospital of the University, Al-Khobar, and Dhahran Eye Specialist Hospital, Dhahran, Saudi Arabia. The medical records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The leading cause of secondary glaucoma was PXG followed by NVG and uveitic glaucoma in this study and it is similar to the study done in Saudi Arabia (23). While other authors (7,12,21,22) found different common subtypes of secondary glaucoma (Table 4). The prevalence of secondary glaucoma varies globally from 0.2 to 26.7% among various studies with varied etiologies (7,11,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The leading cause of secondary glaucoma was PXG followed by NVG and uveitic glaucoma in this study and it is similar to the study done in Saudi Arabia (23). While other authors (7,12,21,22) found different common subtypes of secondary glaucoma (Table 4). The prevalence of secondary glaucoma varies globally from 0.2 to 26.7% among various studies with varied etiologies (7,11,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, it was reported that more males were affected in a study conducted in India (12). On the other hand, more females were affected, as reported in other studies (21)(22)(23). This could be partly due to variations in the common subtypes of secondary glaucoma or other unknown factors.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Here, primary open-angle glaucoma was the most encountered type. Similarly, many studies in Middle Eastern countries like Qatar, Saudi Arabia, and Iran, and in Asia and America reported the same findings [ 10 - 14 ].…”
Section: Discussionsupporting
confidence: 61%
“…A study conducted in Saudi Arabia and recruited 999 participants with glaucoma found that 82.3% of them had bilateral involvement, and primary open-angle glaucoma (27.7%) and secondary glaucoma (26.7%) were the most prevalent types[ 14 ].…”
Section: Introductionmentioning
confidence: 99%